Бренд-комунікації рітейлу FMCG сегменту в Україні у соцмережах під час війни: виклики, тенденції, трансформація бренд-контенту - Куц, Анна Анатоліївна (Київський національний університет імені Тараса Шевченка, 2024)
Робота присвячена вивченню впливу повномасштабного вторгнення в Україну на бренд-комунікації рітейлерів FMCG-сегменту в соціальних мережах. Робота містить огляд соціологічних теорій комунікацій, особливостей технологій комунікацій брендів, зокрема рітейлерів в соціальних мережах. Висвітлено важливі зміни, які відбулися в суспільстві та бізнесі внаслідок війни, а також особливості адаптації підприємств до нових реалій. Проведено дослідження трансформацій в змісті комунікаційних повідомлень, за допомогою контент-аналізу брендкомунікацій АТБ-маркету, найбільшого рітейлера України, в соціальній мережі Instagram.

The study is about the impact of the full-scale invasion of Ukraine on the brand communications of FMCG retailers in social networks. The paper provides an overview of sociological theories of communication, specifics of brand communication technologies, in particular, retailers’ social media. The article highlights important changes that have taken place in society and business because of the war, as well as the specifics of businesses’ attempts to adapt to new realities. The author conducted a research of transformations in the content of communication messages using the content analysis of brand communications of ATB-market, the largest retailer in Ukraine, on the social network Instagram.
Brand communications of FMCG retail segment in Ukraine via social networks in wartime: challenges, trends, transformation of brand content
Keywords: комунікації; бренд-комунікації; рітейл FMCGсегменту; соціальні мережі; війна; communications; brand communications; FMCG retail; social networks; war